The Effectiveness Of Active Carbon From Sawdust Of Coconut For Reduce To Reduce The Lead Waste - Dayana, Indri (CV. PUSDIKRA MITRA JAYA, 2021)
The main objective of this research is the content sawdust of coconut can be processed into activated carbon which can be used to reduce lead waste. The presence of heavy metals in the environment is an environmental problem that needs serious attention. Pollutants are dominated by heavy metal waste, one of which is lead (Pb). PB is classified into dangerous pollutants. In this study, coconut wood powder was used as activated carbon because the price was cheap and could reduce the negative impact on the environment because the sawdust of coconut was a waste in the wood industry. The advantages of activated carbon are its large capacity and absorption, because the pore structure and the presence of chemical functional groups on the surface of activated charcoal such as C = O, C, and CH. The quality of activated carbon is shown by the absorption value of Iod where based on the provisions of SNI 06-3730-1995 the activated carbon is considered to be of high quality if the value of its absorption is close to 750 mg / g.